2013
DOI: 10.1111/apm.12069
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of antibody response and viraemia following natural infection of porcine circovirus 2 (PCV‐2) in a conventional pig herd

Abstract: Porcine circovirus 2 (PCV-2) is a primary agent of post-weaning multi-systemic wasting syndrome (PMWS), ubiquitous in pig herds. The course of viraemia and seroconversion in naturally infected pigs were investigated in piglets from the 2nd week of their life. Piglets were divided into seropositive (Ab(+)) and seronegative (Ab(-)) groups. Subsequently, after vaccination against PCV-2 (Ingelvac(®) CIRCOFLEX™, Böehringer Ingelheim), they were further divided into non-vaccinated seronegative (NVAC/Ab(-)) and serop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…From these papers, 10 were excluded based on in-/exclusion criteria. Accordingly, 13 articles [ 4 , 5 , 7 , 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] were finally considered for data collection ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…From these papers, 10 were excluded based on in-/exclusion criteria. Accordingly, 13 articles [ 4 , 5 , 7 , 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] were finally considered for data collection ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, PCV2 is an endemic and very stable virus [26] that may persist in pens [12] and it has been demonstrated that pigs subclinically infected with PCV2 may excrete medium to high loads of the virus in faeces [21,24]. In addition, C s a n k et al [11] reported the shedding of the virus during subclinical infection in the presence of post-infection antibodies. Hence, these pigs could serve as reservoirs shedding the virus into the environment.…”
Section: Resultsmentioning
confidence: 99%